Exegesis of Legal Rulings on Qs. Al-Muzzammil 20 and Qs. Shad 23-24 and the Derivation of Legal Principles for Mudharabah and Musyarakah Contracts - Mohammad Albi; Hasan Bisri; M Athoillah (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This research analyzes the interpretation of QS. Al-Muzzammil verse 20 and QS. Shad verses 23–24 as well as their istinbat (derivation of legal rulings) related to mudharabah and musyarakah contracts from the perspective of Islamic commercial jurisprudence (fiqh muamalah). The introduction highlights the importance of integrating Qur’anic exegesis studies with Islamic economic law. The method employed is a qualitative study based on the analysis of classical and contemporary tafsir, hadith studies, and ushul fiqh approaches in examining dalalah, qiyas, and maqashid sharia. The findings indicate that QS. Al-Muzzammil verse 20 implicitly legitimizes economic activities and serves as the basis for the permissibility of mudharabah through dalalah isyarah and the principle of facilitation. Meanwhile, QS. Shad verses 23–24 affirm the existence of partnership (syirkah) and warn against potential injustice within cooperation, thus forming an ethical and normative foundation for musyarakah through dalalah taqrir. This study concludes that both verses not only provide a strong sharia basis for mudharabah and musyarakah contracts but also outline the principles of justice, trustworthiness, and public interest (maslahah) as the core foundations of Islamic commercial dealings.